APLIKASI SISTEM INFORMASI TRANSAKSI GADAI PADA PERUM PEGADAIAN KRATON PASURUAN - Rahmawati, Linda Suvi (DINAMIKA DOTCOM, 2013)
Application of Information System is a computerized application that makes it easy to manage information on a insatnsi system, for which the existence of information system applications is the information you need and reports can be easier and faster to process it. Based on observations in the field, indicating that the service process at the pawnshop pawn transaction with existing systems resulting in unfavorable effects on other parts of the system. Both delay delivery of information, assessment periods, and calculations - other computations. Thus the problem - the problem arose rationale for building and designing an information system information system applications pawnshop transaction is expected to improve service on the UPC Kraton Pasuruan. Keywords: Information Systems Applications, Pawnshops